Operasi Psikologi Forensik dalam Penegakan Sistem Hukum Indonesia (Studi Kasus Pembunuhan Angeline di Bali) - Khoyron Nasir, Tomi; Subhandi Bakhtiar, Handar (Journal Evidence Of Law, 2024)
The aims of writing this article is to understand the operation of forensic psychology as a field of psychology or belief emphasizing the application of methods, scientific evidence and psychological concepts in trials by the judiciary in the Indonesian law enforcement. Forensic psychology is a combination of the fields of clinical psychology, social psychology and cognitive psychology, as well as the psychology of the accused himself. In this research the author uses normative legal research methods, namely conducting library research. The problem in this article is how the role of forensic psychology operations can be applied in the trial of certain case in the form of the Angeline murder case in the Indonesian legal system. Then, people involved in forensic psychology are divided into two, the first is forensic psychology scientists and the second is forensic psychology practitioners. While for operational purposes, forensic psychologists are tasked with conducting psychological autopsies, investigative interviews with perpetrators of crimes, interviews with witnesses and families of victims, and identifying perpetrators of crimes. In criminal law in Indonesia, forensic psychologists have contributed as expert witnesses, as expert advisors outside the court or as ad hoc judges, and as educators for criminal justice actors. Although they have different uses or purposes to facilitate the investigation of cases, forensic psychologists have limited purposes in their use in court.